Enfrentamento religioso em situações de sofrimento - Siqueira, Marília Parreiras Maia (2012)
The report aims at understanding how cancer-stricken patients face suffering as a result of the disease through their religiosity/spirituality. Religion is a cultural issue and it is suitable toponder that man should seek spirituality and religion to be enabled to find the true meaning oflife, improve health and deal with adversity and pain. Faith in sacredness and the search forreligious refuge when faced with situations which are beyond personal control can extend topeople the possibility of going way beyond their personal limits and are mechanisms of positive confrontation. On accompanying a cancer-stricken patient through phenomenological and humanistic investigation it was concluded that suffering possesses thepotential of conquering, creativity and transformation. The religious confrontation is enduredas a structural experience which controls and shapes personality, besides bringing relief and meaning to life. The positive religious confrontation based on acceptance, surrender and faithis the source of psychic and existential maturity and a factor of resilience